The Effect of Business Planning and Record on Entrepreneur Success - Formaida Tambunan (RIRAI Publisher, 2021)
The problem that has always been in the government's spotlight is the low number of jobs, so the solution is entrepreneurship. Many food and beverage business people ignore business planning and recording so that it has an impact on the slow and even undeveloped business they run. Therefore, someone who is an entrepreneur needs a business plan and records in order to achieve success in entrepreneurship. The purpose of this study was to determine “The Influence of Business Planning and Records on Entrepreneurial Success. This research is an associative quantitative study with the population being all food and beverage entrepreneurs in Tanjung Rejo Village and the sample is a total population of 57 respondents. The research instrument used was a questionnaire and analyzed using multiple linear regression. The results show that business planning and records have an effect on entrepreneurial success. In connection with the results of this study, it is recommended to all people who want to be entrepreneurs and especially entrepreneurs to always make good plans and keep records of every business activity that is carried out.